Perancangan Sistem Pakar Diagnosis Penyakit Kulit Dengan Menggunakan Algoritma Forward Chaining - NI Wayan Priscila Yuni Praditya; Purnamasari, Evi; Fajri, Ricky Maulana (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The skin is the largest organ of the human body and has an important role to protect the internal organs of the human body from direct external interference such as sunlight and scratches from sharp or blunt objects. Without skin, our bodies will not be formed perfectly. Just like other organs of the body, if the skin is not properly cared for, it will cause skin diseases, although skin diseases are not too dangerous in human life, skin diseases can make humans feel uncomfortable. This skin disease has many types that are almost the same, therefore an expert system is needed to find out what type of skin disease we are likely to experience. This application is made web-based. The method used by this expert system is the Forward Chaining method, in this expert system it will show several questions or symptoms experienced, then after the user answers the available questions, the diagnosis results will appear. Based on the design of the creation and implementation of an expert system to diagnose skin diseases using the forward chaining algorithm, it can be concluded that the expert system for diagnosing skin diseases using the forward chaining algorithm can help in diagnosing skin diseases suffered or experienced by someone, this expert system for diagnosing skin diseases is very useful for many people to find out what type of skin disease they are suffering from considering the many types of skin diseases whose symptoms are almost similar, this expert system is very dependent on the ability of experts (doctors) who are the source of knowledge in research on this skin disease, and the expert system designed is web-based, making it easier for users to diagnose their diseases anywhere and anytime.